EL GÉNERO DICRANOTROPIS FIEBER, 1866, EN LA REPÚBLICA ARGENTINA Y CHILE. (INSECTA: HOMOPTERA: DELPHACIDAE) - Marino de Remes Lenicov, Ana M. (Acta Entomológica Chilena, 2022)
This paper deais with the two known representative of the genus Dicranotropis Fieber, 1866, in Argentina and Chile, D. fuscoterminata (Berg, 1879) and D. acheron Fennah, 1957 respectively. As a result of the study of type specimens from Berg’s collection, in addition to many other collected by the author in several localities from Argentina, Liburnia fuscoterminata Berg in transferred to Dicranotropis and L. nigricula Berg, 1789 synonymized with this species. Specimens collected by Dr. M. Olmi in the type locality of D. acheron, have permitted the description of the female, unknown to date. As D. fuscoterminata and D. acheron are morphologically very similar, both species are comparatively analized and illustrated.